THERMAL REQUIREMENT AND PHENOLOGICAL CHARACTERIZATION OF PAPAYA VARIETIES CULTIVATED UNDER SUBTROPICAL CLIMATE - Silva, Marcelo de Souza; Leonel, Sarita; Souza, Jackson Mirellys Azevêdo; Ferreira, Rafael Bibiano; Modesto, Joyce Helena; Bolfarini, Ana Carolina Batista (IRRIGA, 2019)
THERMAL REQUIREMENT AND PHENOLOGICAL CHARACTERIZATION OF PAPAYA VARIETIES CULTIVATED UNDER SUBTROPICAL CLIMATE MARCELO DE SOUZA SILVA1; SARITA LEONEL2; JACKSON MIRELLYS AZEVÊDO SOUZA2; RAFAEL BIBIANO FERREIRA2; JOYCE HELENA MODESTO2 E ANA CAROLINA BATISTA BOLFARINI2 1 Departamento de Produção Vegetal, Faculdade de Agronomia e Engenharia Florestal – FAEF, Rod. Cmte. João Ribeiro de Barros, Km 420, 17400-000, Garça - SP, Brasil, mace-lo-souza@hotmail.com. 2 1Departament. de Agronomia/Horticultura, Faculdade de Ciências Agronômicas da UNESP, Av. Universitária, nº 3780 - Altos do Paraíso, 18610-03, Botucatu – SP, Brasil, sarinel@fca.unesp.br, jackson.mirellys@hotmail.com, aprigio_bibiano@hotmail.com, joyce_helena_modesto@hotmail.com, anacarolinabolfarini@hotmail.com. 1 ABSTRACT The thermal sum has been widely used to correlate phenological phases of a culture, a technique used to quantify the time required for any phenological phase in any type of environmental conditions, independently of the species. In view of the above, this study aimed to evaluate the thermal requirement and phenological characterization of papaya varieties cultivated under subtropical climate. It was measured the following phenological stages length: from planting to flowering (PF), from flowering to harvest (FH) and from planting to the beginning of harvest (PH), by measuring the time elapsed between each phenological phase. Female and hermaphrodite flowers were considered for measuring the growth curves of fruits by evaluating length (LF) and diameter (DF) of the fruits at 15-day intervals. The thermal requirement was measured by the accumulation of thermal sum in degree-days (DD) during different phenological phases and fruits development period. In current study conditions, it was possible to infer that Sunrise Solo variety and hybrid Tainung nº 1 are earlier, with an approximately 10-month interval between planting and the beginning of the harvest; therefore, necessitating accumulation of 1722.2 and 1798.1 degree-days, respectively. Keywords: Carica papaya L., degree-days, plant performance. SILVA, M. S.; LEONEL, S.; SOUZA, J. M. A.; FERREIRA, R. B.; MODESTO, J. H.; BOLFARINI, A. C. B. EXIGÊNCIA TÉRMICA E CARACTERIZAÇÃO FENOLÓGICA DE VARIEDADES DE MAMOEIRO CULTIVADAS SOB CLIMA SUBTROPICAL 2 RESUMO A soma térmica tem sido amplamente utilizada para correlacionar fases fenológicas de uma cultura, uma técnica utilizada para quantificar o tempo necessário para qualquer fase fenológica em qualquer tipo de condição ambiental, independentemente da espécie. Frente ao exposto, objetivou-se com este estudo avaliar a exigência térmica e caracterização fenológica de variedades de mamoeiro cultivadas sob clima subtropical. Foi mensurado a duração dos seguintes estádios fenológicos: plantio ao florescimento (PF), florescimento à colheita e plantio ao início da colheita, através da aferição do tempo decorrido entre cada fase fenológica. As curvas de crescimento dos frutos, acompanhadas em flores femininas e hermafroditas, foram determinadas mediante avaliação do comprimento e diâmetro dos frutos em intervalos de 15 dias. Já a exigência térmica foi mensurada através do acumulo da soma térmica em graus-dia, durante as diferentes fases fenológicas e para o período de desenvolvimento dos frutos. Nas condições do presente estudo foi possível inferir que a variedade Sunrise Solo e o híbrido Tainung nº1 são mais precoces, com intervalo entre o plantio e o início da colheita de aproximadamente 10 meses, necessitando do acúmulo de 1722,2 e 1798,1 graus-dia, respectivamente. Palavras-chave: Carica papaya L., graus-dia, performance de plantas.